C-Terminal Fibronectin Exerts Beneficial Effects in Reducing Tissue Damage and Modulating Macrophage Function in a Murine Septic Model - Geng H; Wu Y; Chen Y (Dove Medical Press, 2023)
Haili Geng, Yong Wu, Yuanzhong Chen Fujian Institute of Hematology, Fujian Provincial Key Laboratory on Hematology, Fujian Medical University Union Hospital, Fuzhou, Fujian, 350001, People's Republic of ChinaCorrespondence: Yuanzhong Chen, Fujian Institute of Hematology, Fujian Provincial Key Laboratory on Hematology, Fujian Medical University Union Hospital, No. 29 Xinquan Road, Fuzhou, Fujian, 350001, People's Republic of China, Tel +86-13306908368, Email chenyz@mail.fjmu.edu.cn; TP123123gtt@163.comBackground: Fibronectin (FN) can improve organ function and slow the progression of sepsis, but full-length FN is hard to be exacted as a therapeutic.Objective: This study aimed to investigate the beneficial effects of C-terminal heparin-binding domain polypeptide of FN (rhFNHC-36) in a cecal ligation and puncture (CLP)-mediated murine septic model and explore its regulatory effects on macrophages.Methods: Mice were randomly assigned to four groups: unoperated control (Normal), sham operation control (Sham), CLP-operation with intravenous injection of phosphate-buffered saline (CLP+PBS), and CLP-operation with rhFNHC-36 treatment (CLP+rhFNHC-36). Blood and abdominal fluid samples were subjected to bacterial colony formation assays. Organs (liver, spleen, and lung) were undergone histopathological analyses and/or weighed to obtain organ indices. Serum interleukin-6 (IL-6) levels, nitric oxide (NO) release from isolated abdominal macrophages, and chemotactic effect of macrophages were measured with commercial kits. Surface programmed death ligand 1 (PD-L1) expression on macrophages was measured by flow cytometry.Results: Mice in the CLP+PBS group showed a lower survival rate than that in the CLP+rhFNHC-36 group. Improved survival was associated with better clearance of bacterial pathogens, as evidenced by colony formation assays. The CLP-induced decrease in thymus and spleen indices was attenuated by rhFNHC-36 treatments. rhFNHC-36 alleviated sepsis-associated tissue damage in liver, spleen, and lung. CLP-mediated increases in plasma IL-6 levels were reversed by rhFNHC-36 treatment. NO levels in peritoneal macrophages after lipopolysaccharides (LPS)-stimulation in the CLP+rhFNHC-36 group were lower than that in the CLP+PBS group. Notably, macrophages from the CLP+rhFNHC-36 group retained better chemotaxis ability. After LPS challenge, these macrophages had a reduced percentage of PD-L1-positive cells compared to those in the CLP+PBS group.Conclusion: rhFNHC-36 improved survival of mice with CLP-induced sepsis by reducing tissue damage and modulating macrophage function. Our work provides critical insight for developing FN-based and macrophages-targeted therapeutics for treating sepsis.Keywords: fibronectin, heparin-binding domain polypeptide, sepsis, macrophage, cecal ligation and puncture